Replacing Barley and Soybean Meal With By-products, in a Pasture Based Diet, Alters Daily Methane Output and the Rumen Microbial Community in vitro Using the Rumen Simulation Technique (RUSITEC) - Smith, Paul E.; Waters, Sinéad M.; Kenny, David A.; Boland, Tommy M.; Heffernan, John; Kelly, Alan K. (Frontiers in Microbiology, 2020)
Plant based by-products (BP) produced from food and bioethanol industries are human inedible, but can be recycled into the global food chain by ruminant livestock. However limited data is available on the methanogenesis potential associated with supplementing a solely BP formulated concentrate to a pastoral based diet. Therefore the objective of this in vitro study was to investigate the effects of BP inclusion rate (in a formulated concentrate) to a pasture based diet on dietary digestibility, rumen fermentation patterns, methane production and the prokaryotic microbial community composition. Diets consisted of perennial ryegrass and one of two supplementary concentrates, formulated to be isonitrogenous (16% CP) and isoenergetic (12.0 MJ/ME/kg), containing either 35% BP, barley and soybean meal (BP35) or 95% BP (BP95) offered on a 50:50 basis, however starch, NDF and fat content varied. The BPs, included in equal proportions on a DM basis, were soyhulls, palm kernel expeller and maize dried distillers grains. The BP35 diet had greater (P<0.05) digestibility of the chemical constituents DM, OM, CP, NDF, ADF. Greater total VFA production was seen in the BP35 diet (P<0.05). Daily methane production (mmol/day; +22.7%) and methane output per unit of total organic matter digested (MPOMD; +20.8%) were greatest in the BP35 diet (P<0.01). Dietary treatment influenced microbial composition (PERMANOVA; P=0.023) with a greater relative abundance of Firmicutes (adj P<0.01) observed in the BP35. The Firmicutes:Bacteroidetes ratio was significantly reduced in the BP95 diet (P<0.01). The relative proportions of Proteobacteria (adj P<0.01), Succinivibrionaceae (adj P<0.03) and Succinivibrio (adj P=0.053) increased in the BP95 diet. The abundance of Proteobacteria was found to be negatively associated with daily methane production (rs -0.71; P<0.01) and MPOMD (rs -0.65; P<0.01). Within Proteobacteria, the relationship of methane production was maintained with the mean abundance of Succinivibrio (rs -0.69; P<0.01). The abundance of the Firmicutes phyla was found to be positively correlated with both daily methane production (rs 0.79; P<0.001) and MPOMD (rs 0.75; P<0.01). Based on in vitro rumen simulation data, supplementation of an exclusively BP formulated concentrate was shown to reduce daily methane output by promoting a favourable alteration to the rumen prokaryotic community.